Bronchial thermoplasty for moderate or severe persistent asthma in adults (Protocol) (2012)
ABSTRACT: This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: To determine the eKicacy and safety of bronchial thermoplasty in adult patients with bronchial asthma, in terms of improvement of symptoms, quality of life and functional parameters, as well as the reduction in the use of conventional medication, the severity of exacerbations in this population and incidence of side effects.